C Community Law Inclusivity in Energy Transition Regulation in Indonesia - Tjahjani, Joejoen; Nugroho, Fajar Seto; Fitriana, Fatma Indah (Jurnal Independent, 2025)
ABSTRACT Indonesia is currently preparing to make a transition in the energy sector, to achieve Net Zero Emission (NZE). In addition to stakeholders, regulatory support, and real action are needed. Through the G20 meeting, Indonesia is a member of the Just Energy Transition Partnerships (JETP), which subsequently forms the Comprehensive Investment and Policy Plan (CIPP). Policymakers need to develop a legal framework and provide regulatory support for handling climate change, and can ensure the legal inclusivity of affected communities. This paper aims to find out the regulations that regulate the acceleration of the energy transition in Indonesia and an analysis of the legal inclusivity of the community in the regulation of accelerating the just energy transition in Indonesia, with the type of normative juridical research and critical legal studies analysis.As a result of the analysis, the regulations that regulate the acceleration of the energy transition in Indonesia refer to Presidential Regulation No. 112 of 2022, the inclusivity of community law in the regulation of accelerating the just energy transition in Indonesia has several weaknesses, so that substantive rights and policy synchronization must be fulfilled, in order to achieve Indonesia's equitable energy security.